Forma zewnętrzna towarów i produktów jako desygnat ochrony prawnej - Tylec, Grzegorz (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: The article focuses on the legal protection of the form of products and goods against illegal copying. The contents of the article constitute, above all, an attempt to define the notion of the form of goods and products. It has also been aimed to specify limits of the allowed copying of goods within the regulations of the unfair competition law.